Early Results After Coronary Artery Bypass Grafting in Patients With Severe Ischemic Left Ventricular Dysfunction - M. K. Mazanov; P. V. Chernyavsky; M. A. Sagirov; N. M. Bikbova; N. I. Kharitonova; D. V. Chernyshev; A. V. Timerbayev; S. Y. Kambarov (Неотложная медицинская помощь)
Introduction. The number of patients with severe ischemic left ventricular dysfunction (ILVD), who undergo coronary artery bypass, increasing each year. ILVD is an established risk factor for mortality in patients after myocardial revascularization during the early and late postoperative periods.Aim of study. To evaluate the early results of surgical myocardial revascularization in patients with coronary artery disease (CAD) and severe ILVD.Material and methods. The study included 149 patients with coronary artery disease with severe left ventricular dysfunction (ejection fraction (EF) ≤39%), operated from January 2002 to December 2018. different variables were assessed (pre- and postoperative), including LV ejection fraction and end systolic volume index (ESVI).Results. The average age of the patients was 59.36±8.97 years (from 30 to 78 years), 93% of the patients were men. In 28 patients (19%), ILVD developed against the background of myocardial infarction (MI) and in 121 (81%) due to ischemic cardiomyopathy (ICMP) with a history of myocardial infarction. The mean EF before surgery was 36.64±3.17 (from 21 to 39%). In the postoperative period, there was an increase in EF, which averaged 44.92±4.92 (from 36 to 59%) (p value <0.001). The mean LV ESVI before surgery was 60.23±11.52 ml/m2. In the immediate postoperative period ESVI decreased to 46.26±12.40 ml/m2 (the value of p<0.001). The average number of bypass coronary arteries in one patient was 3.9±0.87. There was also a decrease in the degree of mitral regurgitation in most patients after coronary artery bypass grafting (CABG) (p value <0.001). Hospital mortality was 2% (3 patients).Conclusion. Coronary artery bypass grafting in patients with severe ischemic left ventricular dysfunction can be performed with low mortality. Surgical myocardial revascularization can be considered a safe and effective operation for patients with coronary artery disease with a satisfactory condition of the distal coronary arteries, low ejection fraction, and with a predominance of viable myocardium.